Antidepressant Effects of Probucol on Early-Symptomatic YAC128 Transgenic Mice for Huntington’s Disease - Cristine de Paula Nascimento-Castro; Ana Claudia Wink; Victor Silva da Fônseca; Claudia Daniele Bianco; Elisa C. Winkelmann-Duarte; Marcelo Farina; Ana Lúcia S. Rodrigues; Joana Gil-Mohapel; Andreza Fabro de Bem; Patricia S. Brocardo (Neural Plasticity)
Huntington’s disease (HD) is an autosomal dominant neurodegenerative disorder caused by a trinucleotide expansion in the HD gene, resulting in an extended polyglutamine tract in the protein huntingtin. HD is traditionally viewed as a movement disorder, but cognitive and neuropsychiatric symptoms also contribute to the clinical presentation. Depression is one of the most common psychiatric disturbances in HD, present even before manifestation of motor symptoms. Diagnosis and treatment of depression in HD-affected individuals are essential aspects of clinical management in this population, especially owing to the high risk of suicide. This study investigated whether chronic administration of the antioxidant probucol improved motor and affective symptoms as well as hippocampal neurogenic function in the YAC128 transgenic mouse model of HD during the early- to mild-symptomatic stages of disease progression. The motor performance and affective symptoms were monitored using well-validated behavioral tests in YAC128 mice and age-matched wild-type littermates at 2, 4, and 6 months of age, after 1, 3, or 5 months of treatment with probucol (30 mg/kg/day via water supplementation, starting on postnatal day 30). Endogenous markers were used to assess the effect of probucol on cell proliferation (Ki-67 and proliferation cell nuclear antigen (PCNA)) and neuronal differentiation (doublecortin (DCX)) in the hippocampal dentate gyrus (DG). Chronic treatment with probucol reduced the occurrence of depressive-like behaviors in early- and mild-symptomatic YAC128 mice. Functional improvements were not accompanied by increased progenitor cell proliferation and neuronal differentiation. Our findings provide evidence that administration of probucol may be of clinical benefit in the management of early- to mild-symptomatic HD.